ANALISIS PAJAK PENGHASILAN PASAL 21, 23, 25 PT KBS TAHUN 2020 - Nathanael , Joshua; Yuniarwati, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to determine whether the withholding, deposit and reporting of income tax complies with the provisions of the applicable tax laws and regulations in Indonesia according to Articles 21, 23 and 25 of PT KBS.iData collection techniques were determined through field research, interviews, documentation and literature review.iThis type of research is qualitative research using descriptive methods. The results of this study indicate that the withholding and reporting of income tax Articles 21, 23 and 25 of PT KBS are in accordance with the applicable tax regulations.iRegarding taxpayer compliance with filing and reporting requirements, PT KBS experienced delays and corrections in filing and reporting PPh Articles 21 and 23.iThere was no delay in Article 25 of the Income Tax Law and in accordance with KEP-537/PJ/2000.i